First-principles insights on the electronic and optical properties of ZnO@CNT core@shell nanostructure. Issue 1 (December 2018) - Shen, Yang; Yang, Xiaodong; Bian, Yue; Nie, Kuiying; Liu, Songmin; Tang, Kun; Zhang, Rong; Zheng, Youdou; Gu, Shulin
Abstract In recent years, various kinds of ZnO-based core@shell nanomaterials have been paid much attention due to their widespread applications in the fields of physics, chemistry and energy conversion. In this work, the electronic and optical properties of a new type of ZnO-based one-dimensional core@shell nanostructure, which is composed of inner ZnO nanowire and outer carbon nanotube (CNT), is calculated based on the first-principles density functional theory (DFT). Calculation results suggest that the ZnO nanowire encapsulated in (9, 9)-CNT is the most stable structure from the view of formation energy. The interaction between the inner ZnO nanowire and the outer (9, 9) CNT belongs to a weak van der Waals type. The complex structure is found to possess metallicity for the outer (9, 9) CNT and maintain the wide band gap nature for the inner ZnO nanowire. Under the different external strains, the charge redistribution between inner ZnO nanowire and outer CNT caused by electron tunneling leads to the shift of Dirac point and the band narrowing of inner ZnO nanowire. The inner ZnO nanowire only has light absorption in the UV region, which is consistent with its optical property originating from its wide bandgap nature.